Tocopherol in the lipid stability of tilapia (Oreochromis niloticus) hamburgers - dos Santos Fogaça, Fabíola Helena [UNESP]; Sant'Ana, Léa Silvia [UNESP] (Elsevier, 2007)
Presence of tocopherol is effective for fish preservation during frozen storage, inhibiting lipid degradation by oxidation. This work evaluated the antioxidant effects of α-tocopherol in diet and postmortem addition on the final quality of hamburgers produced from tilapia fillets kept frozen for zero, 30, 60, and 90 days. Chemical composition varied within the values found for tilapia fish. The increase in α-tocopherol levels reduced the values of thiobarbituric acid reactive substances (TBARS) in the samples at all time intervals. Tocopherol supplementation in diets protected the hamburgers from lipid oxidation more effectively than postmortem addition. © 2007 Elsevier Ltd. All rights reserved.
Keywords: α-Tocopherol; Antioxidant; Chemical composition; Frozen storage; Supplementation; Tilapia; lipid; thiobarbituric acid reactive substance; tocopherol; antioxidant activity; food freezing; food quality; lipid degradation; lipid oxidation; molecular stability; Oreochromis niloticus